PENGARUH METODE PEMBELAJARAN ROLE PLAYING TERHADAP HASIL BELAJAR SISWA KELAS IV SD NEGERI 10 TANJUNG LAGO - Rodiah; Sholeh, Kabib; Lara Syaflin, Sylvia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the problem of lowstudent learning outcomes, especially in the IPAS subject for fourth grade at SD Negeri 10 Tanjung Lago. The purpose of this study is to determine the effect of the role-playing learning method on the learning outcomes of fourth-grade elementary school students as a resource in the learning process, with the research subjects being students (n=33). This research method is a type of quantitative research using the Quasi Experiment method (quasi-experiment) with the design form in this study being Nonequivalent Control Group Design. Data collection techniques in this study were tests in the form of multiple choice questions (pretest and posttest), observation, interviews, and documentation. Data analysis techniques in this study were normality tests, homogeneity tests, and hypothesis tests. Student learning outcome data were analyzed using the Kolmogorov-Smirnov and Shapiro-Wilk tests with (Sign.) > 0.05. Then continued with the homogeneity test, it was stated that the significance value of the student learning outcomes obtained was 0.341, meaning that the data was homogeneous, namely from the same variant because the sign value was greater than 0.05. Then continued with the data analyzed using the Independent sample t-test on the SPSS version 25 application. The results of the study showed that the role playing method was able to improve student learning outcomes. The results of the hypothesis test showed a Sign value. (2-tailed) 0.001 <0.05 which means Ho is rejected and Ha is accepted with the statement "There is an Influence of the Role Playing Learning Method on the Learning Outcomes of Class IV Of State Elementary School 10 Tanjung Lago".